Современная сетевая поэзия: Интертекстуальность, языковая игра, ирония - Masłowa, Walentina (Acta Polono-Ruthenica, 2006)
In the report the analysis of modern Russian net poetry was made. It separated and defined its speciality and function in cultural space, paying particular attention to intertextuality as a phenomenon typical for the modern literature.